2015
DOI: 10.1007/s12325-015-0264-7
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study to Examine Healthcare Costs Related to Cardiovascular Events in Individuals with Hyperlipidemia

Abstract: IntroductionFew studies have demonstrated the cost burden of cardiovascular events (CVEs) among patients with hyperlipidemia. The primary objective of this study was to determine the mean costs associated with CVEs among patients with hyperlipidemia by follow-up time period. Secondary objectives of this study included characterizing costs by CVE type and coronary heart disease (CHD) risk.MethodsThis retrospective cohort study used longitudinal claims to calculate payer costs according to CHD risk level and typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…In the remaining 15 studies, eight (53%) assessed the costs that could be directly attributed to HF by comparing the costs of patients with HF to those with no HF [ 51 , 69 , 88 , 95 , 104 , 105 , 107 , 111 ]. In the other seven studies [ 46 , 58 , 66 , 68 , 75 , 89 , 94 ], it was inferred that all-cause resource use (i.e., no distinction for HF-related resource use) had been included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the remaining 15 studies, eight (53%) assessed the costs that could be directly attributed to HF by comparing the costs of patients with HF to those with no HF [ 51 , 69 , 88 , 95 , 104 , 105 , 107 , 111 ]. In the other seven studies [ 46 , 58 , 66 , 68 , 75 , 89 , 94 ], it was inferred that all-cause resource use (i.e., no distinction for HF-related resource use) had been included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Sources of resource use and unit costs, currency and cost year, and the methods of resource use valuation (i.e., cost/charge, cost-to-charge ratio) were well defined in all studies. The majority of studies (26/43; 60%) reported adequately on the methodology of estimating costs [ 22 – 24 , 43 , 44 , 49 , 50 , 57 60 , 63 , 66 72 , 75 77 , 85 , 87 , 88 , 116 ]; in 14 (33%), the costing approach was concluded by the information reported and relevant guidelines by Drummond et al [ 91 ], although not explicitly stated [ 25 , 45 47 , 53 – 55 , 64 , 65 , 81 , 86 , 89 , 90 , 118 ]; three studies (10%), only published as abstracts, did not provide any information on the costing methodology [ 34 , 73 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two US claims database Table 5. analyses 6,38 reported a 43% subsequent CV event risk over 2-3 years of follow-up for patients with a history of MI, stroke, UA, or revascularization. CV event risk was 49% over 2 years among a Swedish cohort of patients with a history of CVD 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, various drugs, hormones, and multiple genetic defects affecting energy metabolism can lead to fat deposition in the liver [1]. Hyperlipidemias have produced a worldwide health critical situation and create a substantial burden not only on personal health but also on societies and economies [9]. Therefore, beneficial and secure pharmacological interventions for hyperlipidemia are urgently needed.…”
Section: Introductionmentioning
confidence: 99%